2003
DOI: 10.1097/01.brs.0000083234.62751.7a
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Clinical Trial of Lumbar Instrumented Fusion and Cognitive Intervention and Exercises in Patients with Chronic Low Back Pain and Disc Degeneration

Abstract: Study Design. Single blind randomized study. Objectives. To compare the effectiveness of lumbar instrumented fusion with cognitive intervention and exercises in patients with chronic low back pain and disc degeneration.Summary of Background Data. To the authors' best knowledge, only one randomized study has evaluated the effectiveness of lumbar fusion. The Swedish Lumbar Spine Study reported that lumbar fusion was better than continuing physiotherapy and care by the family physician.Patients and Methods. Sixty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
103
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 529 publications
(107 citation statements)
references
References 54 publications
3
103
0
1
Order By: Relevance
“…In total, 84% of participants achieved some employment since their injury and 74% were working at the time of the survey. These two methods of assessing work outcome have been employed in a number of studies (Trief et al 2000;Brox et al 2003;Price et al 2005), yet the utility of such isolated measures of performance without adjunct information (e.g. work maintenance) is questionable.…”
Section: Discussionmentioning
confidence: 99%
“…In total, 84% of participants achieved some employment since their injury and 74% were working at the time of the survey. These two methods of assessing work outcome have been employed in a number of studies (Trief et al 2000;Brox et al 2003;Price et al 2005), yet the utility of such isolated measures of performance without adjunct information (e.g. work maintenance) is questionable.…”
Section: Discussionmentioning
confidence: 99%
“…Indications comprise degenerative disorders and spondylolisthesis (grades I, II) [20,24,49]. During the last years, lumbar fusion has been increasingly criticised [6], while clinical studies have shown similar long-term follow-up results with conservative treatment [8,14]. Side effects of lumbar fusion include ASD, pseudarthrosis, bone-graft morbidity, high rates of re-operation, implant failure, and sagittal spinal imbalancing.…”
Section: Discussionmentioning
confidence: 99%
“…The goal of a fusion of the lumbar spine is to obtain a primary solid arthrodesis so as to alleviate pain [10,11,14,15,19,22,31]. Different circumferential or ''360°'' fusion techniques have been described such as combined anteriorposterior fusion (APF), instrumented posterior lumbar interbody fusion (PLIF) and transforaminal lumbar interbody fusion (TLIF).…”
Section: Introductionmentioning
confidence: 99%